Acute Toxicity Test of Gastroretentive Mucoadhesive Granule Preparation of Earthworm Flour (Lumbricus rubellus) - Magfirah; Novalia Merue; Joni Tandi; Utami Islamiati (Postgraduate, University of Mataram, 2024)
Earthworms (Lumbricus rubellus) contain the compound lumbricin, which is beneficial for treatment, and its use is still simple, leading to the innovation of gastroretentive mucoadhesive granule formulations. However, its security has not yet been fully supported by research. This research aims to determine the toxic effects caused by earthworm granule preparations in terms of toxicity symptoms and the determination of the LD50 value. This research used 20 male white rats that were randomly divided into 4 groups. One control group was given Aquadest, and three treatment groups were given earthworm granules at doses of 500 mg/kgBB (P1), 2000 mg/kgBB (P2), and 5000 mg/kgBB (P3) with a single oral administration. The research results indicate that the preparation of earthworm granules (Lumbricus rubellus) causes toxic symptoms such as decreased locomotor activity, piloerection, and increased grooming frequency in line with the increase in dosage, but does not result in the death of the test animals. (LD50). Based on the research findings, it can be concluded that the LD50 value of the earthworm granules (Lumbricus rubellus) is >5000 mg/kgBB and falls into the practically non-toxic category with an LD50 range of 5–15 g/kgBB